SIX USM JOURNALS ACCORDED 'CREAM' STATUS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 1 November 2016 Six renowned journals with editors inchief comprising of academicians from Universiti Sains Malaysia (USM) have been accorded the Current Research in Malaysia (CREAM) status by the Ministry of Higher Education (MoHE) based on the standards of excellence evident in the journals.